Fracture Resistance of Endodontically Treated Upper Premolar Teeth Restored With Bulk Fill And Conventional Resin Composite - Çoruh Dulgergil; Mehmet Dallı; Adem Gök (Cumhuriyet University, 2022)
Objectives: The aim of this in vitro study was to evaluate the fracture resistance of endodontically treated upper premolar teeth restored with different resin composites. Materials and Methods: Hundred and eight maxillary premolar teeth were randomly divided into nine groups (n=12). The teeth in the first group were left intact and tested as unprepared group 1 (negative control) (group 1). Other eight groups were prepared with MOD cavities and endodontically treated. The teeth in group 2 (positive control) were unrestored. Other groups were restored with different resin composites. Group 3: conventional resin composite and group 4-9 six bulk fill resin composite (group 4: 3M Filtek Flowable Bulk Fill, group 5: 3M Filtek Posterior Bulk Fill, group 6: Voco X-tra base, group 7: Voco X-tra fil, group 8: Dentsply SDR Flow, group 9: Dentsply Quixfil). Single Bond Universal was applied as self-etch, according to application instructions. The restored teeth were stored in distilled water for 24 hours at 37°C. Compressive force was applied parallel to the long axis of the teeth. The test was carried out at a speed of 1mm/min. ANOVA and Tukey HSD tests were used in the analysis of the data (p,0.05). Results: Conventional resin composite (group 3) showed lower fracture resistance than bulk fill resin composites (p<0.05) . There was no significant difference between the groups restored with bulk fill composites (p≥0.05). Conclusions: The bulk fill composites increase the fracture resistance of endodontic treated teeth,